Economic Growth, Poverty, and Unemployment as Key Determinants of Welfare in Jambi Province - Hastin, Mira; Karimi, Kasman; Putri, Osi Hayuni (Al Dzahab, 2026)
Purpose: This study examines the impact of economic growth, poverty rate, and unemployment rate on community welfare in Jambi Province from 2015 to 2024, measured by the Human Development Index (HDI). The study aims to provide empirical evidence on how these socioeconomic factors collectively and individually influence regional welfare. Design/Methodology/Approach: A quantitative explanatory research design was employed using annual time-series secondary data. Multiple linear regression analysis with the Ordinary Least Squares (OLS) method was applied. To ensure robustness, stationarity tests, cointegration tests, and classical assumption tests were conducted to avoid spurious regression and satisfy econometric requirements. Findings: The results demonstrate that economic growth, poverty, and unemployment have a significant simultaneous effect on community welfare. Partially, economic growth positively affects HDI, poverty exerts a negative impact, and unemployment shows a positive association with HDI during the study period. Research Implications: The findings highlight the importance of comprehensive regional development policies that not only promote economic growth but also focus on poverty alleviation and human capital development through sustained investments in education, healthcare, and social protection. The observed relationship between unemployment and welfare underscores the need for integrated employment strategies aligned with broader human development objectives.